2018
DOI: 10.7897/2277-4343.09124
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of Nicotiana Glauca Graham (Solanaceae) and Its Toxic Effects on Culiseta Longiareolata (Diptera; Culicidae)

Abstract: Nicotiana glauca (N. glauca) (Solanaceae) is an ornamental plant. It has insecticidal properties. However, these uses cannot compensate for the overall negative impacts of this plant. This study was aimed to evaluate the larvicidal effect of the aqueous extract of N. glauca leaves on the 4th stage larva of Culiseta longiareolata (Cs. longireolata). N. glauca leaves were harvested, dried and powdered using an electric mill. Hot aqueous extraction was done with 150 g powdered leaf in 1000 mldistilled water. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…The plant is used in traditional medicine as a diuretic and against rheumatism; it is also a therapeutic and anti-bacterial plant (Ladhari et al 2013). The effect of this species has also been proven against different orders of insects (Doumandji-Mitiche and Doumandji 1993;Ozenda 1991;Aouinty et al 2006;Kemassi and Oueld El-hadj 2008;N'Guessan et al 2009;Lebouz 2010;Kemassi et al 2012;Koita et al 2012;Habbachi et al 2013;Merabti et al 2015;Benhissen 2016;Merabti 2016, Masna 2016Korichi-Almi et al 2016;Almi et al 2016;Benhissen et al 2018;Bekhakheche et al 2018;Seglab et al 2019;Boublata et al 2020;Saadane et al 2021;. For the present study, the plant was collected in the Bousaada region (M'sila, Algeria) (33°48′24″ N latitude, 2°52′56″ E longitude).…”
Section: Cleome Arabica (Capparidaceae)mentioning
confidence: 96%
“…The plant is used in traditional medicine as a diuretic and against rheumatism; it is also a therapeutic and anti-bacterial plant (Ladhari et al 2013). The effect of this species has also been proven against different orders of insects (Doumandji-Mitiche and Doumandji 1993;Ozenda 1991;Aouinty et al 2006;Kemassi and Oueld El-hadj 2008;N'Guessan et al 2009;Lebouz 2010;Kemassi et al 2012;Koita et al 2012;Habbachi et al 2013;Merabti et al 2015;Benhissen 2016;Merabti 2016, Masna 2016Korichi-Almi et al 2016;Almi et al 2016;Benhissen et al 2018;Bekhakheche et al 2018;Seglab et al 2019;Boublata et al 2020;Saadane et al 2021;. For the present study, the plant was collected in the Bousaada region (M'sila, Algeria) (33°48′24″ N latitude, 2°52′56″ E longitude).…”
Section: Cleome Arabica (Capparidaceae)mentioning
confidence: 96%
“…Despite this wide range of effective molecules, the main pests have developed more or less pronounced resistance towards them; this has led to more and more people turning to natural compounds from plants for the development of new insecticidal molecules. The insecticidal activity of aromatic plant extracts has also been confirmed by Jang et al 2002;Habbachi et al 2014;Mahmoudian et al 2002;Habbachi et al 2013;Idrissi-Hassani et al 1998;Abbasi et al 2003;Abbasi et al 2003b;Idrissi-Hassani and Hermas 2008;Abbasipour et al 2010;Masna et al 2016;Benhissen et al 2018).…”
Section: Introductionmentioning
confidence: 71%
“…Also, several studies have highlighted the toxic effect of North African aromatic plants on Diptera such as the effects of Ricinus communis and Tetraclinis articulata on mosquito larvae Culex pipiens (Linné), Aedes caspius (Pallas), Culiseta longiareolata (Aitken) and Anopheles maculipennis (Meigen). Aouinty et al (2006) and Benhissen et al (2018) were studied the C. longiareolata control using Nicotiana Glauca plant. Other studies showed that plants in Maghreb arid areas are the most effective even against the most resistant insects such as locusts (Idrissi Hassani and Hermas 2008;Idrissi et al 1998;Idrissi Hassani 2000;Lebouz 2010;Kemassi and Oueld El-Hadj 2014) or domestic cockroaches (Masna et al 2016).…”
Section: Discussionmentioning
confidence: 99%